The changing geographical coherence of measles morbidity in the United States, 1962-88. - Cliff, A; Haggett, P; Stroup, D; Cheney, E (1992)
Geographical coherence may be defined as the degree to which the behaviour of a time series in one geographical area corresponds with the time series behaviour in another. This paper illustrates the concept using the epidemiological time series of reported monthly measles morbidity for the states of the United States for the 27 years from January 1962 to December 1988. Over this period, as measles morbidity has declined in response to vaccination campaigns, and as the seasonal peaking of the disease in late spring has become less pronounced, the geographical coherence has altered at the national, divisional, regional and state levels. There was a steady decline in coherence from 1962 to 1980. In 1981, a dramatic reduction occurred, but there has been some recovery since. The implications for spatial forecasting models of these reducing levels of coherence are discussed.